The Influence Of Career Planning And Soft Skills On Work Readiness Through Work Motivation As An Intervening Variable In Class XII Students Of SMK 01 PGRI Semarang: THE INFLUENCE OF CAREER PLANNING AND SOFT SKILLS ON WORK READINESS THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE IN CLASS XII STUDENTS OF SMK 01 PGRI SEMARANG - Wahyuningsih, Khofifah Ajeng; Kurniawan, Bayu; Putri, Noventia Karina (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the Influence of Career Planning and Soft Skills on Work Readiness Through Work Motivation as an Intervening Variable in Class XII Students of SMK 01 PGRI Semarang. The benefits of this study are that this study can be used as input in compiling and determining the right HR Management strategy in order to obtain more optimal results for Work Readiness in Class XII Students of SMK 01 PGRI Semarang. The population of the researcher was all students of SMK PGRI 01 Semarang class XII majoring in Financial Accounting Institutions and majoring in Office Management and Business Services. The sampling technique uses non-probability method with a saturated sampling technique. The research sample selection was 145 respondents. Data analysis in this study used SEM analysis with the AMOS version 23 program. The results of the analysis and discussion showed that Career Planning partially influenced Work Readiness. Soft Skills did not influence Work Readiness. Work Motivation influenced Work Readiness. Career Planning influenced Work Motivation. Soft Skills influenced Work Motivation. Career Planning influenced Work Readiness through Work Motivation as an intervening variable. Soft skills influence Work Readiness through Motivation as an intervening variable in grade XII students of SMK 01 PGRI Semarang.